SOCIAL CONFLICT RESOLUTION THROUGH EMPOWERMENT OF LOCAL WISDOMS - Mohammad Jamin (Faculty of Law, Universitas Sebelas Maret, 2020)
Ethnic, religious, race, and cultural diversity, as well as a large number of populations, are a treasure and strength for the Indonesian people, but on the other hand, it can be potential social conflicts that jeopardize the national integrity. Local wisdom which lived generations by generations and owned by the various local community is a social asset that can be empowered in social conflict resolution. Local wisdom plays an important role, not only preventing social conflict but also providing breakthroughs to resolve conflicts that occurred. Law Number 7 of 2012 concerning Social Conflicts Resolution which reflects the principles of local wisdom, it should be more empower those principles into reality. This empowerment can be done by actualizing the values and institutionalize of local wisdom in social conflict resolution that is implemented at the stages of conflict prevention, termination of the conflict, and restoration of post-conflict.